2021
DOI: 10.3390/pr9010089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Parameters on Phenolic Compounds and Color of Cabernet Sauvignon Red Wine Concentrates Obtained by Reverse Osmosis and Nanofiltration

Abstract: In this study, Cabernet Sauvignon red wine was subjected to reverse osmosis and nanofiltration processes at four different pressures (25, 35, 45, and 55 bar) and two temperature regimes (with and without cooling). The aim was to obtain concentrates with a higher content of phenolic compounds and antioxidant activity and to determine the influence of two membrane types (Alfa Laval RO98pHt M20 for reverse osmosis and NF M20 for nanofiltration) and different operating conditions on phenolics retention. Total poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…Aroma compounds were analysed by gas chromatograph with mass spectrometer in obtained retentates and initial wine. In our previous study Cabernet Sauvignon was subjected to process of reverse osmosis and nanofiltration at different pressures and temperature regimes to determine the influence of RO and NF membranes on phenolics and colour compounds retention [28].…”
Section: Introductionmentioning
confidence: 99%
“…Aroma compounds were analysed by gas chromatograph with mass spectrometer in obtained retentates and initial wine. In our previous study Cabernet Sauvignon was subjected to process of reverse osmosis and nanofiltration at different pressures and temperature regimes to determine the influence of RO and NF membranes on phenolics and colour compounds retention [28].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [2,[6][7][8] have reported that the phenolic profile of ecologically produced wine differs from the phenolic profile of conventionally produced ones, comparing the same grape variety. Phenolic compounds originate from the seeds and skins of grapes, and they are transferred into must during crushing, maceration or fermentation [9]. Therefore, the grape maturity and health, climate, the use of fertilizers or other adjuvants, harvest conditions and vinification techniques greatly affect the final concentrations of the mentioned compounds [10].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the reverse osmosis membranes, nanofiltration ones have slightly larger pore size that decreases the retention of bioactive compounds. However, at the same operating conditions, the permeate flux during nanofiltration is higher, the process duration time is shorter and membrane fouling is less severe than during the reverse osmosis process, which lowers the production cost [9]. The nanofiltration wine permeate contains mainly water and ethanol, but several low weight molecules can also pass through membranes, such as acetic and lactic acid, or some aroma compounds [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations